Den nya juden och judiska exilen i Judisk Tidsskrift 1933–1950 - Englund, Anders (Nordisk judaistik, 1996)
This article is a study of a Swedish-Jewish periodical by the name of Judisk Tidsskrift ("The Jewish Periodical") published in the years 1928-1966. The article is focusing on the period 1933-1950, years which were so crucial for the history of Sweden and the rest of the world and in particular for the Jewish people. The main focus of the article is two questions which were given extensive space during these years: ‘The New Jew’ and Jewish exile. The main authors of the articles on these subjects were the chief Rabbi of Stockholm during this period, Marcus Ehrenpreis, who was also the editor of the periodical, and Hugo Valentin, a historian and one of the leading Zionists in Sweden.